Magnetism in quasi-two-dimensional tri-layer La2.1Sr1.9Mn3O10 manganite - Jeetendra Kumar Tiwari (Nature Portfolio, 2021)
Abstract The tri-layer La $$_{3-3x}$$ 3 - 3 x Sr $$_{1+3x}$$ 1 + 3 x Mn $$_{3}$$ 3 O $$_{10}$$ 10 manganites of Ruddlesden–Popper (RP) series are naturally arranged layered structure with alternate stacking of ω-MnO $$_2$$ 2 (ω = 3) planes and rock-salt type block layers (La, Sr) $$_2$$ 2 O $$_2$$ 2 along c-axis. The dimensionality of the RP series manganites depends on the number of perovskite layers and significantly affects the magnetic and transport properties of the system. Generally, when a ferromagnetic material undergoes a magnetic phase transition from ferromagnetic to paramagnetic state, the magnetic moment of the system becomes zero above the transition temperature (T $$ _{C} $$ C ). However, the tri-layer La $$_{2.1}$$ 2.1 Sr $$_{1.9}$$ 1.9 Mn $$_{3}$$ 3 O $$_{10}$$ 10 shows non-zero magnetic moment above T $$ _{C} $$ C and also another transition at higher temperature T $$ ^{*} ≈ $$ ∗ ≈ 263 K. The non-zero magnetization above T $$ _{C} $$ C emphasizes that the phase transition in tri-layer La $$_{2.1}$$ 2.1 Sr $$_{1.9}$$ 1.9 Mn $$_{3}$$ 3 O $$_{10}$$ 10 not a ferromagnetic to paramagnetic state. We show here the non-zero magnetic moment above T $$ _{C} $$ C is due to the quasi-two-dimensional nature of the tri-layer La $$_{2.1}$$ 2.1 Sr $$_{1.9}$$ 1.9 Mn $$_{3}$$ 3 O $$_{10}$$ 10 manganite. The scaling of the magnetic entropy change confirms the second-order phase transition and the critical behavior of phase transition has been studied around T $$_C$$ C to understand the low dimensional magnetism in tri-layer La $$_{2.1}$$ 2.1 Sr $$_{1.9}$$ 1.9 Mn $$_{3}$$ 3 O $$_{10}$$ 10 . We have obtained the critical exponents for tri-layer La $$_{2.1}$$ 2.1 Sr $$_{1.9}$$ 1.9 Mn $$_{3}$$ 3 O $$_{10}$$ 10 , which belong to the short-range two-dimensional (2D)-Ising universality class. The low dimensional magnetism in tri-layer La $$_{2.1}$$ 2.1 Sr $$_{1.9}$$ 1.9 Mn $$_{3}$$ 3 O $$_{10}$$ 10 manganite is also explained with the help of renormalization group theoretical approach for short-range 2D-Ising systems. It has been shown that the layered structure of tri-layer La $$_{2.1}$$ 2.1 Sr $$_{1.9}$$ 1.9 Mn $$_{3}$$ 3 O $$_{10}$$ 10 results in three different types of interactions intra-planer ( $$ J_{ab} $$ J ab ), intra-tri-layer ( $$ J_{c} $$ J c ) and inter-tri-layer ( $$ J' $$ J ′ ) such that $$ J_{ab}> J_{c}>> J' $$ J ab > J c > > J ′ and competition among these give rise to the canted antiferromagnetic spin structure above T $$ _{C} $$ C . Based on the similar magnetic interaction in bi-layer manganite, we propose that the tri-layer La $$_{2.1}$$ 2.1 Sr $$_{1.9}$$ 1.9 Mn $$_{3}$$ 3 O $$_{10}$$ 10 should be able to host the skyrmion below T $$ _{C} $$ C due to its strong anisotropy and layered structure.